Nursing Care Management for Mrs. R After Cesarean Section Surgery in the Merpati Ward of Dr. S. Hardjolukito Air Force Hospital: Asuhan Keperawatan Pada Ny. R Dengan Post Operasi Sectio Caesarea (Sc) Di Ruang Merpati RSPAU Dr. S. Hardjolukito - Rizamil , Puspita; Sari, Dwi Agustiana; -, SASTRA GANDHI ARAB (Sahabat Publikasi Kuu, 2025)
Background Every woman wants her labor to go smoothly and be able to give birth a perfect baby. Labor can go normally, but sometimes it meets an obstacle so it has to be conducted by surgery. Assistances for labor surgery by section caesarea has a long history (Prihartini & Iryadi ,2019). Theory Sectio caesarea is a surgery to give birth to a fetus through an incision in the abdominal wall and artificial labor uterus, so that the fetus is born through the stomach and abdominal wall and uterine wall so that the child is born intact and healthy (Warniati & Nuryani, 2019). Priority diagnosis Acute pain. Nursing intervention Perform non-pharmacological techniques to reduce pain (deep breathing techniques) Nursing Implementation Provide non-pharmacological techniques to reduce pain (deep breathing technique). Nursing Evaluation There was an effect of decreasing the pain scale to 2 while the expected pain scale was 0. It can be concluded that the problem was only partially resolved.